-16=-4(2+4x)-2(7x+4)

Simple and best practice solution for -16=-4(2+4x)-2(7x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16=-4(2+4x)-2(7x+4) equation:



-16=-4(2+4x)-2(7x+4)
We move all terms to the left:
-16-(-4(2+4x)-2(7x+4))=0
We add all the numbers together, and all the variables
-(-4(4x+2)-2(7x+4))-16=0
We calculate terms in parentheses: -(-4(4x+2)-2(7x+4)), so:
-4(4x+2)-2(7x+4)
We multiply parentheses
-16x-14x-8-8
We add all the numbers together, and all the variables
-30x-16
Back to the equation:
-(-30x-16)
We get rid of parentheses
30x+16-16=0
We add all the numbers together, and all the variables
30x=0
x=0/30
x=0

See similar equations:

| 2x/40=5/4x | | .15x+.93=107.27 | | 2x+6(1/6)=1 | | 100=x130 | | 2w+2(w+4.75)=129.5 | | 5x-2.6=x+8.2 | | -6(-2x+4)+2(x+6)=72 | | 4(.25+c)=1.8 | | 2x-5x-65=35 | | 12.5=a+5.5 | | 515+c=223 | | 15x/12=16÷24 | | x-0.23x=50000 | | (H-x)^3-3(H-x)(K-S*x)^2+2(K-S*x)^3=0 | | 2(6r+5)=14-(7r-4)+11r | | 5(-1/9)+8y=-5 | | 14+13y=20y-2 | | 4(5y=2)=48 | | 1/9+3y=24 | | 0.9v-30.61=3.5(0.8+7.6v) | | 8x+4(1.5x)=800 | | x+6/4=3 | | 1.5x-x=0.x-1.2 | | x+9/9=-3 | | 8*x+20-(6*x+18)=0 | | 2(6w-1)=8w | | s+1.5s+10=64 | | 3x/6=7 | | 2.5=x^-3 | | 1x-6x=8 | | 0=3(x–5)(2x+3) | | 3(4y-2)+15=12y+9 |

Equations solver categories